Penyulingan Minyak Nilam - Liliek Suparmi (Balai Besar Kimia dan Kemasan, 1979)
The amount of the oil as well as the quality are influenced by among others pretretment of the fresh leafe. distilation methode , density of the leaf mass, temperature, steam pressure, and time of distillation. The quality of the oil are evaluated trough their spesific gravity, optical rotation, ester number, acid number and solubility in alcohol.